The Effect of Service Quality and Accessibility on Taxpayer Compliance of Rural and Urban Land and Building Tax Payment Week Program in Yogyakarta City - Ahmadi, Sigit; Puterisari, Dwi Utami (International Journal Labs, 2025)
The Rural and Urban Land and Building Tax (PBB-P2) constitutes a strategic source of Regional Original Revenue (PAD) for local governments. However, taxpayer compliance remains a challenge despite various programs implemented by the Yogyakarta City Regional Financial and Asset Management Agency (BPKAD), including the PBB-P2 Payment Week Program. This study aims to analyze the effect of service quality and accessibility on taxpayer compliance in the Rural and Urban Land and Building Tax (PBB-P2) Payment Week program in Yogyakarta City. The research employs a quantitative approach with an explanatory research design. The population consists of 1,000 PBB-P2 taxpayers in Yogyakarta City, with a sample of 286 respondents determined using the Slovin formula and accidental sampling technique. The data collection instrument employed a 4-point Likert scale questionnaire tested for validity and reliability. The analysis technique used multiple linear regression with SPSS version 30.0. Results show: (1) service quality has a positive significant effect on compliance (regression coefficient 0.225; sig. 0.000 < 0.05); (2) accessibility has a positive significant effect on compliance (regression coefficient 0.170; sig. 0.000 < 0.05); (3) simultaneously, both variables have significant effects (F value 93.698; sig. 0.000 < 0.05); (4) an Adjusted R² value of 0.394 indicates 39.4% of compliance variation is explained by service quality and accessibility. The practical implication suggests BPKAD Yogyakarta City needs to optimize service quality dimensions and improve accessibility through digitalization and provision of inclusive facilities.